Spyware and adware - Aycock, John Daniel 1970- (Advances in information security, 2011)
Spyware and Adware introduces detailed, organized, technical information exclusively on spyware and adware, including defensive techniques. This book not only brings together current sources of information on spyware and adware but also looks at the future direction of this field. Spyware and Adware is a reference book designed for researchers and professors in computer science, as well as a secondary text for advanced-level students. This book is also suitable for practitioners in industry.